"I Have a Hippopotamus!": Preparing Effective Early Childhood Environmental Educators. Issue 3 (3rd July 2017) - Torquati, Julia; Leeper-Miller, Jennifer; Hamel, Erin; Hong, Soo-Young; Sarver, Susan; Rupiper, Michelle
ABSTRACT: This article describes an early childhood teacher-preparation program that infuses environmental education and nature experiences into courses, practicum, and student-teaching experiences. Program philosophy, pedagogy, materials, and methods are described and linked to the Early Childhood Environmental Education Programs: Guidelines for Excellence, the Guidelines for the Preparation and Professional Development of Environmental Educators, and state-level early learning guidelines that focus on connecting young children with nature. Preservice teachers build knowledge, skills, and dispositions for effective environmental education beginning from an awareness level and progressing to application and refinement. The value of nature is communicated explicitly and implicitly throughout the program. Preliminary analysis of student outcomes indicated that, over the course of the program, students' ratings of the importance of nature and science experiences and outcomes increased, along with their confidence implementing environmental-education activities.